Perbuatan Melawan Hukum Terhadap Pembongkaran Bangunan Atas Objek Sewa Menyewa - Max Gilberth Emillio Veerman; Merry Tjoanda; Sarah Selfina Kuahaty (Faculty of Law Universitas Pattimura, 2026)
Acts against the law can be interpreted in Article 1365 of the Civil Code stated that